2020
DOI: 10.18823/asiatefl.2020.17.3.11.921
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Text Difficulty across Grades in Korean Middle School English Textbooks Using Coh-Metrix

Abstract: This study aims to investigate the text difficulty of the reading materials of Korean middle school English textbooks with Coh-Metrix, a software developed by the Institute for Intelligent Systems at the University of Memphis to analyze the linguistic and psycholinguistic features of English text and textbooks with a wide range of indices on cohesion and language. In this study, the textbook corpus consisted of the text files extracted from 13 English textbooks. These files were used for analyzing the text dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…These findings were confirmed by some previous studies which revealed that teacher talk addressed to the lower proficiency learners consists of shorter sentences than that to those of higher proficiency. Ryu and Jeon (2020) revealed that sentence length is an indicator of sentence difficulty. Long sentences contain more complicated concepts and ideas, thus, becoming complex and more difficult to perceive (Zipoli, 2017).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…These findings were confirmed by some previous studies which revealed that teacher talk addressed to the lower proficiency learners consists of shorter sentences than that to those of higher proficiency. Ryu and Jeon (2020) revealed that sentence length is an indicator of sentence difficulty. Long sentences contain more complicated concepts and ideas, thus, becoming complex and more difficult to perceive (Zipoli, 2017).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The value of Coh-Metrix has been demonstrated in more than 50 published research studies (e.g., Crossley, Greenfield & McNamara, 2008;Crossley, Salsbury & McNamara, 2009;Duran, McCarthy, Graesser & McNamara, 2006;Kim & Lim, 2019;Ryu & Jeon, 2020). For example, studies using Coh-Metrix have been able to distinguish between highcohesion and low cohesion texts (McNamara, Ozuru, Graesser & Louwerse, 2006), analyze authentic and simplifies texts for L2 material development (Crossley, Louwerse, McCarthy & McNamara, 2007), and evaluate intelligent tutoring system dialogues (Wolfe, Widmer, Torrese & Dandignac, 2018).…”
Section: Coh-metrixmentioning
confidence: 97%
“…Oveshkova [5] developed a task and activity system based on the English corpus and took the students of a foreign language college as the experimental object to observe the effect of the language learning method based on the corpus [5]. Ryu et al [6] investigated the textual difficulty of reading materials of English textbooks in Korean middle schools and analyzed the linguistic and psycholinguistic characteristics of English texts and textbooks by constructing an English reading corpus [6]. From the above studies, we can see that the current research direction of the English reading corpus is basically the research on its function, and the basic framework of the English reading corpus, such as vocabulary and word attributes, is rarely researched and analyzed.…”
Section: Introductionmentioning
confidence: 99%